THE INFLUENCE OF COMPETENCE, DISCIPLINE AND WORK STRESS ON EMPLOYEE PERFORMANCE IN PT ARTHA CENTRA BANGUN PERKASA MEDAN - Hendry; Angelyn; Harsandi; Hutanico, Hunianti; Jeffry; Delano, Chandra (STIE Kusuma Negara, 2020)
The purpose of this study was to analyze the decline in employee performance at PT Artha Centra Bangun Perkasa. HR plays an important role in achieving the goals of the organization or company. Therefore HR is required to be professional, and efficient in facing challenges and opportunities. In this case, the organization or company must pay attention to the competence and discipline of each employee. Competence shows the expertise possessed to carry out the task, and competency coupled with discipline will show a sense of responsibility. Apart from these two things, work stress also affects the decline in a person's performance because it causes physical and psychological disorders. The total population of 35 people and 30 people from companies engaged in the same industry for the validity test. The method used is quantitative with quantitative descriptive research, using interviews, questionnaires and study documentation. Multiple linear regression, coefficient of determination and simultaneous testing to be used in the analysis method. The results of the study have shown that competency, discipline and work stress simultaneously and partially have a positive effect on employee performance.